Universal primers for the amplification and sequence analysis pf actin-1 from diverse mosquito species - Staley, Molly; Dorman, Karin S.; Bartholomay, Lyric C.; Fernández Salas, Ildefonso; Farfán Ale, José Arturo; Loroño Pino, María Alba; García Rejón, Julián Everardo; Ibarra Juárez, Luis Arturo; Blitvich, Bradley J. (American Mosquito Control Association, 2010)
We report the development of universal primers for the reverse-transcription polymerase chain reaction (RT-PCR) amplification and nucleotide sequence analysis of actin cDNAs from taxonomically diverse mosquito species. Primers specific to conserved regions of the invertebrate actin-1 gene were designed after actin cDNA sequences of Anopheles gambiae, Bombyx mori, Drosophila melanogaster, and Caenorhabditis elegans. The efficacy of these primers was determined by RT-PCR with the use of total RNA from mosquitoes belonging to 30 species and 8 genera (Aedes, Anopheles, Culex, Deinocerites, Mansonia, Psorophora, Toxorhynchites, and Wyeomyia). The RT-PCR products were sequenced, and sequence data were used to design additional primers. One primer pair, denoted as Act-2F (5′-ATGGTCGGYATGGGNCAGAAGGACTC-3′) and Act-8R (5′-GATTCCATACCCAGGAAG-GADGG-3′), successfully amplified an RT-PCR product of the expected size (683-nt) in all mosquito spp. tested. We propose that this primer pair can be used as an internal control to test the quality of RNA from mosquitoes collected in vector surveillance studies. These primers can also be used in molecular experiments in which the detection, amplification or silencing of a ubiquitously expressed mosquito housekeeping gene is necessary. Sequence and phylogenetic data are also presented in this report.